Sleep disturbance and use of screens in different stages of quarantine in provinces of Patagonia argentina - Santander , Mauro D.; Posadas-Martínez, María Lourdes; Puga, María Celeste; Ontiveros, Hernán; Zúñiga, Marco; Gutiérrez, Manuel; García , Gastón (Revista del Hospital Italiano de Buenos Aires, 2022)
Introduction: due to the pandemic developed by COVID 19, the Argentine Government adopted, as of March 20, 2020, exceptional measures of social, preventive and mandatory isolation (ASPO) or quarantine in order to protect public health. In this stage, there was a greater use of screens that in excess, constitutes a risk factor for cardiovascular diseases and alteration in the quality of sleep.Methods: two Surveys were conducted, in the third and eighth week of quarantine, on behaviors and life habits in people between 13-80 years of age. They were self-administered and sent through social networks. The sampling was random. The data were analyzed using the SPSS® statistical package. The surveys were anonymous and confidential.Results: 3386 responses were obtained. It was obtained that the amount of daily hours in front of screens and the hours of sleep and the onset of sleep were different by groups of pre, third and eighth week of quarantine. The adolescent groups howed greater differences in all variables with respect to the pre-quarantine period. The correlation between the hours of screen and the hours of sleep was low, in the 3 stages of quarantine.Conclusion: this study estimated the change in habits during quarantine. In quarantine, longer hours of sleep, a delay in the time of onset of sleep and more hours in front of screens were observed, these differences being significant with respect to the pre-quarantine period, with the greatest differences being established in adolescents.
Keywords: COVID-19; sleep initiation; quarantine; sedentary behavior